Activation of the α7 nicotinic acetylcholine receptor upregulates blood-brain barrier function through increased claudin-5 and occludin expression in rat brain endothelial cells. (16th February 2019) - Kimura, Ikuya; Dohgu, Shinya; Takata, Fuyuko; Matsumoto, Junichi; Kawahara, Yohei; Nishihira, Megumi; Sakada, Shohei; Saisho, Takuya; Yamauchi, Atsushi; Kataoka, Yasufumi
Highlights: α7 nAChR agonist tightens the brain endothelial tight junction barrier. α7 nAChR agonist increases claudin-5 and occludin in brain endothelial cells. Varenicline and nicotine (non-selective nAChR agonist) do not exhibit these effects. Brain endothelial α7 nAChR is a positive regulator of blood-brain barrier function. Abstract: The blood-brain barrier (BBB) is formed by brain endothelial cells (BECs) and regulates brain homeostasis by restricting the entry of blood-borne substances into the brain. Recent in vivo studies have shown that administration of nicotinic acetylcholine receptor (nAChR) agonists protects against BBB disruption and neuroinflammation induced by stroke and traumatic brain injury through the systemic cholinergic anti-inflammatory pathway. In the present study, we focused on the nAChRs expressed on BECs rather than those widely expressed in the central nervous system and peripheral tissues, and examined whether activation of the nAChRs on BECs facilitates BBB function. We used primary cultures of rat brain endothelial cells to evaluate brain endothelial permeability and tight junction (TJ)-related protein expression after a 24-h exposure to PHA543613 (a selective α7 nAChR agonist) or 5-iodo-A-85380 (a selective α4β2 nAChR agonist). We found that PHA543613 decreased sodium fluorescein permeability and increased the expression levels of claudin-5 and occludin, key TJ components. In contrast, 5-iodo-A-85380 had no effect on brain endothelial permeability or TJ protein expression. These findings suggest that the selective activation of α7 nAChRs on BECs has a specific role in upregulating BBB properties through increased claudin-5 and occludin expression.